2018
DOI: 10.30556/jtmb.vol14.no2.2018.395
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi keterdapatan unsur logam tanah jarang dalam abu batubara Pusat Listrik Tenaga Uap Ombilin, Sumatera Barat

Abstract: ABSTRAKLogam Tanah Jarang (LTJ) merupakan sumber material penting dari abad ke-21, banyak digunakan sebagai penunjang kehidupan modern seperti mobil listrik, perangkat identifikasi kesehatan (MRI, X-ray, Scanner, contrast agent, dll), LCD, hard drive komputer, pembangkit listrik tenaga angin, teknologi hijau, perangkat night vision, sistem radar dan peralatan militer. Unsur LTJ antara lain terdapat pada abu hasil pembakaran batubara dari Pembangkit Listrik Tenaga Uap (PLTU). Potensi produksi abu batubara dari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
7
0
3
Order By: Relevance
“…Then the ash was physically concentrated that based on density and magnetism differences using shaking table and magnetic separator. The silicate minerals, especially quartz (SiO 2 ), has a density of 2.7 g/cm 3 , the magnetite 5.15 g/cm 3 , alumina silicate (Al 2 O 3 , SiO 2 ) 3.69 g / cm 3 while the coal ash itself has a density of about 2.23 g/cm 3 (Suganal, Umar and Mamby, 2018). The light minerals move to the tailing part while the heavy one stays on the concentrate part.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the ash was physically concentrated that based on density and magnetism differences using shaking table and magnetic separator. The silicate minerals, especially quartz (SiO 2 ), has a density of 2.7 g/cm 3 , the magnetite 5.15 g/cm 3 , alumina silicate (Al 2 O 3 , SiO 2 ) 3.69 g / cm 3 while the coal ash itself has a density of about 2.23 g/cm 3 (Suganal, Umar and Mamby, 2018). The light minerals move to the tailing part while the heavy one stays on the concentrate part.…”
Section: Methodsmentioning
confidence: 99%
“…If the value > 2.5 then the separation would be run easily. The formula of concentration criteria is presented as follows (Rodliyah, 2017) The research of coal ash from the Ombilin power plant reported that the REE-bearing mineral in the fly ash from that power plant is monazite (Suganal, Umar and Mamby, 2018). According to the CC value of monazite and silica (3.0) that is higher than that of the minimum limit of the CC, the content increase of La, Ce, Pr, Sm, and Nd are due to its association in monazite as shown in Table 9 and Figure 7.…”
Section: Enrichment Process Of Ree Content From Coal Gasification Ashmentioning
confidence: 99%
“…Penggunaan LTJ saat ini sangat beragam, umumnya untuk industri yang menggunakan teknologi tinggi (Suganal et al, 2018). (Suganal dkk., 2018).…”
Section: Latar Belakangunclassified
“…Berbagai penelitian terkait kandungan LTJ pada abu batubara sudah dilakukan, khususnya pada PLTU Ombilin Sumatera Barat [4], PLTU Banjarsari di Sumatera Selatan [5], PLTU di Kalimantan Timur [1] dan PLTU di kawasan Indonesia Timur [6]. Penelitian kandungan LTJ pada abu batubara limbah PLTU di luar negeri sudah banyak, misalnya di China, PLTU di Jepang salah satunya kandungan LTJ totalnya adalah 420 mg/kg [7], PLTU Kentucky di AS 1.213,6-1.667,6 mg/kg [8], PLTU di US kandungan LTJ-nya lebih dari 700 ppm [9], PLTU lain di AS kandungan rata-rata logam La, Y dan Sc sebesar 591 mg/kg [10] dan berbagai PLTU lainnya.…”
Section: Pendahuluanunclassified
“…Awalnya dalam batubara input bahan bakar PLTU kadar LTJ-nya rendah setelah terkonsentrasi menjadi dominan. Hal ini sejalan dengan hasil penelitian yang dilakukan Suganal dkk [4] pada PLTU Ombilin dan penelitian Firman dkk [5] pada PLTU Banjarsari Sumatera Selatan.…”
Section: D) Kandungan Ltj Abu Batubaraunclassified